Use of multi-strain probiotics in linseed meal based diet for Labeo rohita fingerlings - Shahzad,M. M. (2023)
Abstract Unavailability of probiotics in fish digestive system fingerlings is unable to digest and absorb their food properly. The current research was conducted to investigate the influence of probiotics added Linseed meal based (LMB) diet on hematology and carcass composition of Labeo rohita juveniles. Hematological parameters are essential diagnostics used to estimate the health status of fish. The usage of probiotics for fish health improvement is becoming common due to the higher demand for environment-friendly culture system in water. Linseed meal was used as a test ingredient to prepare six experimental test diets by adding probiotics (0, 1, 2, 3, 4 and 5 g/kg) and 1% indigestible chromic oxide for seventy days. According to their live wet weight, five percent feed was given to fingerlings twice a day. Fish blood and carcass samples (Whole body) were taken for hematological and carcass analysis at the end of the experiment. The highest carcass composition (crude protein; 18.72%, crude fat; 8.80% and gross energy; 2.31 kcal/g) was observed in fish fed with test diet II supplemented with probiotics (2 g/kg). Moreover, maximum RBCs number (2.62× 106mm-3), WBCs (7.84×103mm-3), PCV (24.61), platelets (63.85) and hemoglobin (7.87) had also been reported in the fish fingerlings fed on 2 g/kg of probiotics supplemented diet. Results indicated that probiotics supplementation has a critical role in improvement of fingerlings’ body composition and hematological indices. Present findings showed that probiotics supplementation at 2 g/kg level in linseed by-product-based diet was very useful for enhancing the overall performance of L. rohita fingerlings.